1969
DOI: 10.1103/physrevlett.22.1366
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Quantized Magnetic Flux in a Superconducting Hollow Cylinder with an Electron Interferometer

Abstract: curves for large Q, which must persist to some extent when noise is included, is the occurrence of a sharp rise in voltage ("instability") at a value of X considerably smaller than xmity.It should be noted that the parameter Q is independent of the area of the junction, depending only on the thickness of the junction, the temperature, and the materials involved. The parameter y, by contrast, is proportional to the area of the junction.We are grateful to Professor M. J. Stephen for posing this problem to us, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The results obtained at present concern the observation of shadow patterns, or out-of-focus images, a t the edges of thick specimens (Blackman, Curzon and Pawlowicz 1963, Goringe and Valdrd 1964, Boersch, Bostanjoglo, Lischke, Niedrig and Schmidt 1966, Watanabe and Ishikawa 1967 Valdrd 1968, 1971) and of the detection of the presence of fluxons in bulk samples by means of interference techniques making use of biprisms (Wahll969, 1970, Lischke 1969, Boersch and Lischke 1970, Lischke 1970a. All the attempts to observe contraat effects due to fluxons in transmission electron microscopy have, however, so far failed ; this is probably due to the following facts : (i) no systematic and thorough attempt has been made because of the complexity and difficulty of the experiments ; (ii) the lack of theoretical data on the optimum working conditions ; (iii) a lack of experimental data on the properties of thin superconducting films.…”
Section: On the Possibility Of Observing Fluxons By Transmissionmentioning
confidence: 97%
“…The results obtained at present concern the observation of shadow patterns, or out-of-focus images, a t the edges of thick specimens (Blackman, Curzon and Pawlowicz 1963, Goringe and Valdrd 1964, Boersch, Bostanjoglo, Lischke, Niedrig and Schmidt 1966, Watanabe and Ishikawa 1967 Valdrd 1968, 1971) and of the detection of the presence of fluxons in bulk samples by means of interference techniques making use of biprisms (Wahll969, 1970, Lischke 1969, Boersch and Lischke 1970, Lischke 1970a. All the attempts to observe contraat effects due to fluxons in transmission electron microscopy have, however, so far failed ; this is probably due to the following facts : (i) no systematic and thorough attempt has been made because of the complexity and difficulty of the experiments ; (ii) the lack of theoretical data on the optimum working conditions ; (iii) a lack of experimental data on the properties of thin superconducting films.…”
Section: On the Possibility Of Observing Fluxons By Transmissionmentioning
confidence: 97%
“…When an electron is passing along side a solenoid, a change in the energy of the electromagnetic field arises due to the overlapping of the magnetic field produced by that electron and the magnetic field of the solenoid. In analogy to the two-tube electrostatic experiment, a relative classical lag ∆L = eΦ/mv takes place for electrons (m=mass, v=velocity) passing on opposite sides of the solenoid thus producing exactly the same phase shift ∆ϕ = 2π∆L/λ, (λ is the electron wave length), of equation 1 revealed in the experiments described before (Möllenstedt & Düker, 1956;Fowler et al, 1961;Boersch et al, 1962;Möllenstedt & Bayh, 1962;Schaal et al, 1966;Lischke, 1969;Matteucci & Pozzi, 1978;Matteucci et al, 2003).…”
Section: Interpretation Of Interference Pattern Shifts: Quan-tum Topomentioning
confidence: 95%
“…We recall only the most significant experiments to show the different strategies adopted to localize the magnetic field in the interferometer (for a review see Peshkin & Tonomura (1989), Olariu & Popescu (1985)). With reference to Figure 3, they are grouped as follows: i) the magnetic field S, produced by a ferromagnetic whisker or by a thin solenoid is located in the geometrical shadow of the biprism wire (Möllenstedt & Düker, 1956;Möllenstedt & Bayh, 1962), ii) a thin iron whisker (Schaal et al, 1966;Fowler et al, 1961) or, alternatively, a superconductor hollow cylinder (Lischke, 1969) replaces the biprism fiber and, at the same time, acts as a source of magnetic field, iii) the shadow region of the wire W in Figure 3 is vacuum coated with a thin ferromagnetic layer L (Fowler et al, 1961;Matteucci & Pozzi, 1978). The main rebuttal to all these experiments regards the fact that electrons move, respectively, through the stray field of the whiskers, solenoids, etc.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the experiments for measuring Φ 0 which can be used to constrain α, paper [21] has found that the quantum of the magnetic flux trapped in a hollow superconductor is πh/e ± 4%. In this experiment, the area is S ≈ 3 × 10 −8 cm 2 , therefore, we will have…”
Section: The Flux Quantizationmentioning
confidence: 99%